2013
DOI: 10.1159/000351937
|View full text |Cite
|
Sign up to set email alerts
|

Richard Guy and His Collaborators: ‘Crackling' the Skin Code

Abstract: This paper aims to summarize the contributions of Richard Guy and collaborators to the skin field. Major contributions have been areas such as the modelling of skin absorption, use of spectroscopic techniques (Fourier transform infrared spectroscopy, attenuated total reflectance Fourier transform infrared spectroscopy and impedance spectroscopy) to characterize the skin barrier and the effects of enhancing techniques on the membrane, dermatopharmacokinetics and assessment of topical bio-availability, iontophor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 130 publications
(205 reference statements)
0
3
0
Order By: Relevance
“…Animal models were not perfect; mice, rat and rabbit models in particular are limited as they do not accurately represent the structure of human skin, the best current model in terms of dermal structure and underlying mechanisms is the pig [ 16 , 35 , 44 ]. The field of dermocosmetics and our increased knowledge about the architecture of skin has led to an enhancement and refinement of a number of in vitro, in vivo and in silico techniques to aid skin research, [ 9 , 11 ] which can be adapted to study a range of conditions in order to more accurately study both human skin disease [ 34 ] and aid drug development [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Animal models were not perfect; mice, rat and rabbit models in particular are limited as they do not accurately represent the structure of human skin, the best current model in terms of dermal structure and underlying mechanisms is the pig [ 16 , 35 , 44 ]. The field of dermocosmetics and our increased knowledge about the architecture of skin has led to an enhancement and refinement of a number of in vitro, in vivo and in silico techniques to aid skin research, [ 9 , 11 ] which can be adapted to study a range of conditions in order to more accurately study both human skin disease [ 34 ] and aid drug development [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] These research activities were stimulated by experiments which showed that nanoparticles penetrated e±ciently through the blood-brain barrier. 5 However, a commercial product for nanoparticle-assisted delivery of drugs through the cutaneous barrier is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…6 It turned out that most of the TiO 2 was located on the skin surface, with small amounts of TiO 2 also being detected in deeper layers of the stratum corneum. Subsequently, the location of the hair follicles on the stripped tapes could be visualized by staining them with OsO 4 . 6 It could be shown that in the deeper layers of the stratum corneum, the TiO 2 particles were detectable only in the orices of the hair follicles.…”
Section: Introductionmentioning
confidence: 99%